One-Step Nucleic Acid Amplification in Breast Cancer Sentinel Lymph Node: A Single Institutional Experience and a Short Review - Brambilla, Tatiana; Fiamengo, Barbara; Tinterri, Corrado; Testori, Alberto; Grassi, Massimo Maria; Sciarra, Amedeo; Abbate, Tommaso; Gatzemeier, Wolfgang; Roncalli, Massimo; Di Tommaso, Luca (Frontiers in Medicine, 2015)
Sentinel lymph node (SLN) examination is a standard in breast cancer patients, with several methods employed along its 20-years history, the last one represented by OSNA. The latter is a intra-operative molecular assay searching for CK19 mRNA as a surrogate of metastatic cells. Our 3-years experience with OSNA (1122 patients) showed results overlapping those recorded in the same Institution with a morphological evaluation (930 patients) of SLN. In detail the data of OSNA were almost identical to those observed with standard post-operative procedure in terms of patients with positive SLN (30%) and micrometastatic/macrometastatic involvement of SLN (respectively 38-45% and 62-55%). By contrast when OSNA was compared to the standard intra-operatory procedure it was superior in terms of accuracy, prompting the use of this molecular assay as a very valid and reproducible for intra-operative evaluation of SLN. Further possibilities prompting the use of OSNA range from adhesion to quality control programs, saving of medical time, ability to predict, during surgery, additional nodal metatastis and molecular bio-banking.